2020
DOI: 10.3390/nu12030764
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Zinc Deficiency in Japanese Patients on Peritoneal Dialysis: Comparative Study in Patients on Hemodialysis

Abstract: Background: It is known that patients on hemodialysis (HD) are prone to developing zinc deficiency due to removal of zinc by HD, inadequate dietary intake, and reduced gastrointestinal zinc absorption. However, the prevalence of zinc deficiency in patients on peritoneal dialysis (PD) has not been well established. Methods: Serum zinc levels were compared between 47 patients on PD and 47 patients on HD matched for age, sex, and duration of dialysis. A serum zinc level < 60 μg/dL was defined as clinical zinc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 41 publications
1
8
1
Order By: Relevance
“…Some clinic investigations also showed that zinc supplements ameliorates TNFα,IL-1beta and Hs-CRP in hemodialysis patients [39]. However, in those studies, no signi cant correlation was found of serum zinc levels with peritoneal dialysis adequacy [9,40]. In this study we found that zinc levels in whole blood are signi cantly different between patients with high tKt/V patients and those with low tKt/V patients.…”
contrasting
confidence: 49%
See 2 more Smart Citations
“…Some clinic investigations also showed that zinc supplements ameliorates TNFα,IL-1beta and Hs-CRP in hemodialysis patients [39]. However, in those studies, no signi cant correlation was found of serum zinc levels with peritoneal dialysis adequacy [9,40]. In this study we found that zinc levels in whole blood are signi cantly different between patients with high tKt/V patients and those with low tKt/V patients.…”
contrasting
confidence: 49%
“…Peritoneal dialysis (PD) patients are in poorer nutrition situation compared to patients on hemodialysis (HD) due to the loss of albumin in the PD e uent [7,8]. Zinc de ciency is common and prevalent in PD patients due to inadequate dietary intake, tubular reabsorption impairment, hypo-proteinemia, reduced gastrointestinal zinc absorption and remove from the PD e uent [9]. There are several cross-section studies revealing the prevalence of zinc in peritoneal dialysis patients worldwide including Japan, Mexico, United states and European countries [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zinc is reported to play a crucial role in the immune According to a study by Satoshi Shimizu and colleagues, the prevalence of clinical zinc deficiency in the hemodialysis population was about 46.4%. They indicated that even patients who have undergone hemodialysis for a short duration showed signs of zinc deficiency and immune disorders (9). We found a higher prevalence of zinc deficiency among hemodialysis patients (57.83%).…”
Section: Discussionmentioning
confidence: 42%
“…Serum Zn levels tend to be low in patients undergoing hemodialysis because these patients are often undernourished owing to chronic inflammation, uremia, and food restrictions. Shimizu et al reported that the mean serum Zn level in Japanese patients undergoing hemodialysis was 61 ± 10.5 μg/dL, and half of all patients had serum Zn levels < 60 μg/dL [11]. In our hospital,4 0% of all patients had serum zinc levels < 60 μg/dL (data not shown).…”
Section: Discussionmentioning
confidence: 44%